A contribution to MRI safety testing related to gradient‐induced heating of medical devices. Issue 2 (28th March 2022) - Arduino, Alessandro; Bottauscio, Oriano; Chiampi, Mario; Zanovello, Umberto; Zilberti, Luca
Abstract : Purpose: To theoretically investigate the feasibility of a novel procedure for testing the MRI gradient‐induced heating of medical devices and translating the results into clinical practice. Methods: The concept of index of stress is introduced by decoupling the time waveform characteristics of the gradient field signals from the field spatial distribution within an MRI scanner. This index is also extended to consider the anisotropy of complex bulky metallic implants. Merits and drawbacks of the proposed index of stress are investigated through virtual experiments. In particular, the values of the index of stress evaluated for realistic orthopedic implants placed within an ASTM phantom are compared with accurate heating simulations performed with 2 anatomic body models (a man and a woman) implanted through a virtual surgery procedure. Results: The manipulation of the proposed index of stress allows to identify regions within the MRI bore where the implant could affect the safety of the examinations. Furthermore, the conducted analysis shows that the power dissipated into the implant by the induced eddy currents is a dosimetric quantity that estimates well the maximum temperature increase in the tissues surrounding the implant. Conclusion: The results support the adoption of an anisotropic index of stress to regulate the gradient‐induced heating of geometrically complex implants. They also pave the way for a laboratory characterization of the implants based on electrical measurements, rather than on thermal measurements. The next step will be to set up a standardized experimental procedure to evaluate the index of stress associated with an implant.